Three-dimensional evaluation of tongue position and volume in adult patients with different skeletal malocclusions - CHIOU Wei-Cho, MEN Xinrui, ZHANG Kaiwen, JIANG Xiaoge, CHEN Song (口腔疾病防治)
Objective To analyze the relationship between tongue volume, tongue position, dental and skeletal parameters in adult patients with different skeletal malocclusions, providing references for the etiology, diagnosis, and treatment of skeletal malocclusions. Methods This study has been reviewed and approved by the Ethics Committee, and informed consent has been obtained from patients. Cone-beam computed tomography (CBCT) and cephalometric radiographs were collected from 60 adult patients, divided into three groups based on ANB angle values: skeletal Class I (0° < ANB < 4°), II (ANB > 4°), and III (ANB < 0°), with 20 cases in each group. Dental and skeletal parameters were measured using Dolphin software. Mimics software was used for 3D reconstruction of the tongue, oral cavity, and upper airway to measure tongue position, tongue volume, oral cavity volume, and upper airway volume, followed by statistical analysis. Results The skeletal Class III group had significantly larger tongue and oral cavity volumes than the skeletal Class I and Class II groups (P = 0.02). Tongue length in the skeletal Class III group was also greater than in the skeletal Class I and Class II groups (P = 0.016). There was no significant difference in the ratio of tongue volume/oral cavity capacity among the three skeletal malocclusion groups (P > 0.05). Tongue volume was positively correlated with U1-SN and negatively correlated with overbite and overjet (P < 0.05). Additionally, tongue volume showed a significant positive correlation with Go-Gn and Pg-Np (P < 0.01), as well as with maxillary and mandibular dental arch width and basal bone arch width (P < 0.01). Upper airway volume was positively correlated with TT-VRL and TP-VRL (P < 0.05). Conclusion Patients with skeletal Class III malocclusion have larger tongue volumes and longer tongues. Patients with larger tongue volumes may also have larger, more forward-positioned mandibles. Patients with more posterior tongue positions may have smaller upper airway volumes. When developing orthodontic or orthognathic treatment plans, it is crucial to consider the relationship between tongue position, tongue volume, the jaws, and the airway to ensure optimal outcomes for both dental and orofacial function.